Effects of Bowen Technique in Postural Neck Pain among Dentists - Nida Aslam, Yasir Kazmi, Ayesha Maqbool, Muhammad Usman Khalid, Muhammad Hassan, Haroon Mansha, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Prolonged forward neck posture is one of the common sources for neck pain among Dentists. Conventional physical therapy and Bowen technique are effective in treating the postural neck pain. Bowen technique is another form of soft tissue mobilization technique. Aim: To determine the effects of Bowen technique in postural neck pain among dentists. Methodology: A quasi study was conducted at Ibn e Siena Hospital Multan, 04 November 2020 to 03 April 2021. It consisted of 58 participants with postural neck pain, randomly allocated into experimental and control groups. The experimental group received Bowen technique and control group received conventional therapy. Assessments were taken at baseline and post treatment using study tools: Numeric pain rating scale (NPRS), Neck disability index (NDI) and goniometer. Results: The mean age of all the participants in experimental and control groups were 36.86± 8.91, 41.44±8.75 respectively. Pre treatment values of NPRS mean rank for experimental and control groups were 28.64, 30.36 respectively. Post treatment NPRS mean rank for experimental and control groups were 26.02 and 32.98 respectively with non-significant p value. Pre treatment values for NDI mean rank experimental and control groups 29.84 29.16. Post treatment NDI mean rank for experimental and control groups were 28.52 30.48 respectively with non-significant p value. Conclusion: Bowen technique is equally effective as conventional therapy for improving postural neck pain. Keywords: Bowen technique (BT), Conventional therapy (CT), Dentists, Neck Pain, Posture.